Laboratory Study of the Impact of Repetitive Electrical and Mechanical Stimulation on Brown Shrimp Crangon crangon. Issue 1 (1st January 2016) - Soetaert, Maarten; Verschueren, Bart; Chiers, Koen; Duchateau, Luc; Polet, Hans; Decostere, Annemie
Abstract: Pulse trawling is currently the best available alternative to beam trawling in the brown shrimp Crangon crangon and Sole Solea solea (also known as Solea vulgaris ) fisheries. To evaluate the effect of repetitive exposure to electrical fields, brown shrimp were exposed to the commercial electrodes and pulse settings used to catch brown shrimp (shrimp startle pulse) or Sole (Sole cramp pulse) 20 times in 4 d and monitored for up to 14 d after the first exposure. Survival, egg loss, molting, and the degree of intranuclear bacilliform virus (IBV) infection were evaluated and compared with those in stressed but not electrically exposed (procedural control) and nonstressed, nonexposed (control) brown shrimp as well as brown shrimp exposed to mechanical stimuli. The lowest survival at 14 d (57.3%) occurred in the Sole cramp pulse treatment, and this was significantly lower than in the group with the highest survival, the procedural control (70.3%). No effect of electrical stimulation on the severity of IBV infection was found. The lowest percentage of molts occurred in the repetitive mechanical stimulation treatment (14.0%), and this was significantly lower than in the group with the highest percentage of molts, the procedural control (21.7%). Additionally, the mechanically stimulated brown shrimp that died during the experiment had a significantly larger size than the surviving individuals. Finally, no effect of the shrimp startle pulse was found. Therefore, it can be concluded that repetitive exposure to a cramp stimulus and mechanical stimulation may have negative effects on the growth and/or survival of brown shrimp. However, there is no evidence that electrical stimulation during electrotrawls would have a larger negative impact on brown shrimp stocks than mechanical stimulation during conventional beam trawling. Received November 15, 2015; accepted May 16, 2016